MG132 Attenuates the Replication of Classical Swine Fever Virus in vitro - Chen, Yuming; Fan, Shuangqi; Zhao, Mengpo; Wu, Keke; Zhu, Erpeng; Ma, Shengming; He, Wencheng; Deng, Shaofeng; Xu, Hailuan; Zhang, Jingyuan; Ding, Hongxing; Yi, Lin; et al. (Frontiers in Microbiology, 2020)
The 26S proteasome, in charge of intracellular protein degradation, plays significant roles in the modulation of various cellular activities as well as in the interplay between virus and host. However, studies about the relationship between 26S proteasome and classical swine fever virus (CSFV) is limited up to now. MG132 is a proteasome inhibitor and has been extensively used in studies about replication of many viruses. Herein, we investigated the role of MG132 in CSFV replication and results showed that MG132 significantly decreased virus titers and viral RNA copies in CSFV-infected PK-15 cells. Further studies demonstrated that MG132 upregulated the expression of several interferon-stimulated genes (ISGs), in CSFV-infected cells. Since the activation of ISGs is controlled by the JAK-STAT signal pathway, we next examined the effect of MG132 on the expression and localization of key molecular STAT1 in the infected cells using Western blot and confocal laser scanning microscopy, respectively. Results showed that CSFV infection and viral NS4A protein decreased the protein level of STAT1, and MG132 promoted the accumulation of STAT1 in the nucleus of cells adjacent to the CSFV-infected cells. Besides, MG132 did not affect the expressions of IFN-α, STAT1, Mx1, OAS1, and PKR genes in cells without CSFV. In conclusion, we identify that MG132 significantly inhibits CSFV replication in vitro, in which the activation of the JAK-STAT pathway and the subsequent upregulation of expressions of ISGs might play significant roles, providing a potential preventive method for CSF.